ChemInform Abstract: An Efficient Protocol for the Cross‐Metathesis of Sterically Demanding Olefins. Issue 47 (4th November 2013) - Wang, Zhen J.; Jackson, W. Roy; Robinson, Andrea J.
Abstract by using the second generation of the Hoveyda—Grubbs catalyst